The Greenish Flower Phenotype of Habenaria radiata (Orchidaceae) Is Caused by a Mutation in the SEPALLATA-Like MADS-Box Gene HrSEP-1 - Mitoma, Mai; Kanno, Akira (Frontiers in Plant Science, 2018)
In Arabidopsis thaliana, the E-class SEPALLATA (SEP) genes are generally expressed across all floral whorls. These genes play fundamental roles in floral organ fate determination during development by interacting with other MADS-box gene products, such as those from A-, B-, and C-class genes. However, the function of SEP genes in orchid remains obscure. Here, we analyzed a mutant orchid cultivar with greenish flowers in Habenaria radiata and found that this phenotype is caused by the absence of SEP function. Wild type H. radiata flowers contain a column and two perianth whorls consisting of three greenish sepals, two white petals, and a lip (labellum). By contrast, the flowers of H. radiata cultivar ‘Ryokusei’ appear greenish, with three normal sepals in whorl 1, two greenish petals and a lip in whorl 2, and several sepaloid organs and a ventral column in whorls 3 and 4. We isolated two SEP-like genes (HrSEP-1 and HrSEP-2) and two AGAMOUS-like genes (HrAG-1 and HrAG-2) from wild type H. radiata and compared their expression in the wild type vs. the mutant cultivar. HrAG-1 and HrAG-2 were expressed in the column in the wild type, whereas these genes were expressed in the ventral column and in sepaloid organs that had been converted from a column in ‘Ryokusei’. HrSEP-1 and HrSEP-2 were expressed in all floral organs in the wild type. However, in the mutant cultivar, HrSEP-2 was expressed in all floral organs, while HrSEP-1 expression was not detected. Thus, we analyzed the genomic structures of HrSEP-1 in the wild type and ‘Ryokusei’ and identified a retrotransposon-like element in its first exon in ‘Ryokusei’. Yeast two-hybrid assays demonstrated that HrSEP-1 interacts with HrDEF, HrAG-1, and HrAG-2. These results indicate that the mutant phenotype of ‘Ryokusei’ flowers is caused by the loss of function of HrSEP-1. Therefore, this gene plays an important role in column, lip, and petal development in H. radiata flowers.